Mediating Effects of Financial Innovations between Behavioral Factors and Financial Inclusion of Micro Enterprises in Kenya - Byegon, Gladys; Cheboi, Josephat; Bonuke, Ronald (SEISENSE (PRIVATE) LIMITED, 2019)
Purpose: Understanding the mediating role of the adoption of financial innovations on the relationship behavioral factors and utilization of formal financial services was the main aim of this research. The behavioral factors examined were self-control, confidence and social proof. The study is premised on behavioral finance theories. Design/Methodology: The positivist approach and explanatory research designs were adopted to understand the relationships between the variables under investigation. A sample of 486 owners/managers of licensed micro-enterprises in Nairobi, Kenya were selected using stratified random sampling technique. Primary data was collected through a structured questionnaire. Hypotheses were tested using Hayes and Zhao approach for mediation analysis. Findings: The results showed that financial innovations mediated the relationship between each of the behavioral factors and financial inclusion, that is; self- control (β =.0941, ρ= .00), confidence; (β = .1019, ρ = .00) and social proof (β = .1036, ρ = .00). Practical implications: The study has brought into fore the mediating role of financial innovations on the relationship between the three behavioral factors and financial inclusion. Thus, practitioners are encouraged give due attention to behavioral factors and financial innovations in policy formulation and programs geared towards optimal utilization of financial services.